Mobile money, agricultural marketing, and off-farm income in Uganda - Haruna Sekabira; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
Mobile money (MM) services can contribute to welfare gains in smallholder farm households. Previous research showed that one important pathway is through higher remittances received from relatives and friends. Here, the role of other impact pathways is examined, especially focusing on agricultural marketing and off-farm economic activities. The analysis builds on panel data from smallholder coffee farmers in Uganda. Regression models show that the adoption of MM technology has contributed to higher household incomes and consumption levels. Off-farm income gains are identified to be an important pathway, also beyond remittances. Typical off-farm income sources are small businesses in trade, transport, and handicrafts, which benefit from novel savings and money transfer opportunities through MM. In terms of agricultural marketing, MM users sell a larger proportion of their coffee as shelled beans to buyers in high-value markets, instead of selling to local traders immediately after harvest. MM services help reduce cash constraints and facilitate transactions with buyers from outside local regions. In conclusion, MM can contribute to rural development through various important pathways. Analysis of adoption patterns suggests that MM services are socially inclusive.
Keywords: O12; O16; O33; Q12; 330; mobile phones; rural banking; smallholder farmers; impact evaluation; Africa